Triging Student Learning Results with Utilizing Google Classroom and Zoom Platform - Mahendra, I Wayan Eka (Universitas Pendidikan Ganesha, 2021)
This research was conducted because the students' science learning outcomes were not optimal during online learning using the WA group. Google classroom and virtual meetings using zoom are indispensable as a combination for implementing online learning using various platforms. This research was conducted at SD Negeri Gugus 6 Batubulan, Sukawati Gianyar, involving a sample of 92 class VI students using simple random sampling technique. Student learning outcomes data in science were collected by tests that had been tested for content validity, empirical validity, and reliability coefficient. The analysis technique used in this study is the one-way ANACOVA, that had been tested the normality of data distribution, linearity regression, and the homogeneity of variants. The results of this study indicate that there are differences in science learning outcomes between students who take online learning using a combination of google classroom and zoom, with students who take online learning using WA group after controlling the prior knowledge variable.